2014
DOI: 10.1093/nar/gku950
|View full text |Cite
|
Sign up to set email alerts
|

The Genomes OnLine Database (GOLD) v.5: a metadata management system based on a four level (meta)genome project classification

Abstract: The Genomes OnLine Database (GOLD; http://www.genomesonline.org) is a comprehensive online resource to catalog and monitor genetic studies worldwide. GOLD provides up-to-date status on complete and ongoing sequencing projects along with a broad array of curated metadata. Here we report version 5 (v.5) of the database. The newly designed database schema and web user interface supports several new features including the implementation of a four level (meta)genome project classification system and a simplified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
251
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(251 citation statements)
references
References 22 publications
0
251
0
Order By: Relevance
“…The fixation probability F can be approximated by FðxÞ ≈ sðxÞ 1 − e −NesðxÞ , [2] where N e is the effective population size (16). The effective population size is estimated for each prokaryotic group from the dN/dS ratio (Methods).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fixation probability F can be approximated by FðxÞ ≈ sðxÞ 1 − e −NesðxÞ , [2] where N e is the effective population size (16). The effective population size is estimated for each prokaryotic group from the dN/dS ratio (Methods).…”
Section: Resultsmentioning
confidence: 99%
“…The tight spacing of protein-coding genes likely results from a combination of the deletion bias and purifying selection that efficiently eliminates nonfunctional, noncoding sequences. T he majority of bacterial and archaeal genomes are small, at least compared with the genomes of multicellular and many unicellular eukaryotes (1,2). Also, with the exception of deteriorating genomes of some parasitic bacteria, the prokaryotic genomes are highly compact, with densely packed protein-coding genes and a low fraction of noncoding sequences (3).…”
mentioning
confidence: 99%
“…6 Large-scale genome sequencing projects are now providing significant insights into the sizes and metabolic functions of the genomes of a wide variety of pure cultures of microorganisms , JimenezInfante, Ngugi et al 2014, Reddy, Thomas et al 2015, Salipante, Roach et al 2015. The outcome of size analysis of sequenced prokaryotic genomes revealed that there is high variability in genome size between and within species.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The Genomes OnLine Database (GOLD) that monitors sequencing projects worldwide has grown from just 1575 sequencing projects in 2005 to over 70,000 in 2015 (Reddy et al 2015). This is partly caused by a rapid drop in the price of high-throughput sequencing (Hayden 2014), but also an increase of free user-friendly bioinformatical tools such as MG-RAST (Meyer et al 2008), MEGAN (Huson et al 2016) and user fora such as seqanswers.com, biostars.org etc.…”
Section: Introductionmentioning
confidence: 99%